2004
DOI: 10.1097/01.mcg.0000128935.48082.f9
|View full text |Cite
|
Sign up to set email alerts
|

Tomato-based Functional Food as Interferon Adjuvant in HCV Eradication Therapy

Abstract: Results demonstrated that the authors' functional food reduces the severity of ribavirin-related anemia and improves the tolerance to the full dose of ribavirin in patients with chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It is able to affect the lipoprotein metabolism by restoring the altered levels of lipid-metabolizing enzymes and stabilizing the arrangement of lipoprotein levels during experimentally induced hepatitis. Another study demonstrated that the regular use of our carotenoid-based functional food minimizes the severity of ribavirin-induced anemia in patients with CHC and improves tolerance to the full dose of antiviral therapy [60]. It was found that a mixture of various carotenoids particularly lycopene seems to be promising for the prevention of liver cancer in hepatitis virus-infected patients with cirrhosis [61,62].…”
Section: Lycopene and Chronic Liver Diseasesmentioning
confidence: 97%
“…It is able to affect the lipoprotein metabolism by restoring the altered levels of lipid-metabolizing enzymes and stabilizing the arrangement of lipoprotein levels during experimentally induced hepatitis. Another study demonstrated that the regular use of our carotenoid-based functional food minimizes the severity of ribavirin-induced anemia in patients with CHC and improves tolerance to the full dose of antiviral therapy [60]. It was found that a mixture of various carotenoids particularly lycopene seems to be promising for the prevention of liver cancer in hepatitis virus-infected patients with cirrhosis [61,62].…”
Section: Lycopene and Chronic Liver Diseasesmentioning
confidence: 97%
“…About antioxidant-rich functional food, our research groups (Vitaglione et al, 2007b;Morisco et al, 2004) developed a FSMP consisting of a tomato paste enriched with extra-virgin olive oil. Carotenoids contained in this FSMP were demonstrated to be highly bioavailable both in healthy subjects and in patients with HCV infection.…”
Section: A New Perspective: Fsmp For Liver Healthmentioning
confidence: 99%
“…Recently, also the use of FSMP as coadjuvant of pharmacological therapies received great attention in the scientific literature. Probiotics in the treatment of transplantations [29] and liver diseases [30] as well as the use of antioxidant-rich foods to counteract antiviral drug oxidative stress [31] represent some interesting examples of the advantage that patients could take from the use of FSMP. Patient associations recommend the development of this kind of foods as their use is perceived as more natural and better tolerated than pills.…”
Section: Food Intended For Special Medical Purposes (Fsmp)mentioning
confidence: 99%